STRATEGY OF FINANCIAL SECTOR DEVELOPMENT AS AN ECONOMIC STUDY OBJECT - Прохоренко, Валерій (Socio-economic relations in the digital society, 2019)
In the article the research, generalization and refi nement of the categorical-terminological apparatus concerning the strategy of financial sector development was conducted. The necessity of using the system approach to the definition of the concept «strategy» is proved. A generalization of the notions of domestic and foreign scholars of the concept of «strategy» was made and author’s interpretation was proposed. The author’s interpretations of the concept of «development» are generalized. Th e connection between the content filling of the concepts «strategy» and «development» is revealed. The essence of the concept of «financial strategy» is explored and their classification is given. Th e concept of «strategy of financial sector development» is formed. Structural-logical scheme of interpretation of the concept «strategy of financial sector development» is constructed.